An introduction to Middle East politics - MacQueen, Benjamin (London : SAGE Publications, 2017)
This new edition of An Introduction to Middle East Politics continues to provide an expansive survey of Middle East politics, thoroughly revised and restructured in response to events currently taking place. Written in a lively and accessible manner, MacQueen takes students on a tour of the region's modern political history up to the present, clearly signposting key events and issues. Providing comprehensive coverage of all key themes in Middle East politics, this book covers: historical legacies, The Ottoman Empire, WWI, colonialism and the Cold War, nationalism and Islamist politics, authoritarianism in Egypt, Algeria and Syria, political changes in Iran, the politics of oil in Saudi Arabia and the Gulf States, Israel, the Palestinians and the Arab States, The Syrian conflict including regional ramifications and particular focus on the Syrian refugee crisis. Each chapter includes a timeline, learning objectives, study questions and annotated further reading and the book finishes with a glossary. Contemporary and fascinating, with dedicated material on culture, gender, ethnicity and minorities, this book is a crucial companion for students of Middle East politics.
Keywords: elektronické knihy; electronic books; Politics & International Relations -- Political Science & International Relations